Veinte obras de arquitectura de la ultima decada : Concurso FV/Ferrum. - Museo Nacional de Bellas Artes, Buenos Aires; Glusberg, Jorge (Buenos Aires : MNBA - Museo Nacional de Bellas Artes Buenos Aires, 1998)
Altuna, Enrique ; Alvarez, Mario Roberto ; Arquitectos, Aslan y Ezcurra ; Arquitectos, Baudizzone - Lestard - varas ; Arquitectos, Benadon Berdichevsky Cherny ; Arquitectos, Chiurazzi / Diaz / Diaz / ; Arquitectos, Diego Felix San Martin - Juan Martin Lonné ; Arquitectos, Gramatica / Guerrero / Morini / Pisani / Urtubey ; Arquitectos, Hampton / Rivoira ; Arquitectos, Lier-Tonconogy ; Arturi, Patricia T. ; Asociados, Arquitecto Jorge D. Turjanski y ; Asociados, Dujovne - Hirsch y ; Asociados, Juan Carlos Lopez y ; Beitia, Pablo Tomas ; Carlos Marinai - Maria H. Perez Maraviglia, Arquitectos ; Hampton / Rivoira, Arquitectos ; Manteola, Sanchez Gomez, Santos, Solsona, Sallaberry Arquitectos ; Ott, Carlos A. ; Pelli, César ; Peralta Ramos SEPRA Arquitectos ; Roca, Miguel Angel ; Sallaberry, Juan Carlos Lopez y Asociados en sociedad con Dujovne - Hirsch y Manteola - Sanchez Gomez - santos - Solsona - ; Sallaberry, Urgell - Fazio - Penedo - Urgell y Manteola - Sanchez Gomez - Santos - Solsona - ; Testa, Clorindo ; Vinoly, Rafael
Veinte obras de arquitectura de la ultima decada, Museo Nacional de Bellas Artes, Buenos Aires, noviembre 1998
Spaans
boek